ANALISIS TAFSIR TENTANG PERINTAH MEMBACA DALAM QS. AL-'ALAQ AYAT 1 DAN RELEVANSINYA TERHADAP PENDIDIKAN ISLAM - Fikri Rabbani; Al Fizkra; Redi Hariadi; Seldi (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2026)
Surah Al-‘Alaq, verse 1, was the first revelation revealed to the Prophet Muhammad (peace be upon him) and contains the command to read (iqra’), which forms the cornerstone for the development of knowledge in Islam. This verse not only emphasises the importance of reading as a means of acquiring knowledge, but also highlights the close connection between the pursuit of knowledge and divine values. This study aims to analyse the interpretations of exegetes regarding the command to read in Surah Al-'Alaq, verse 1, to identify the educational values contained therein, and to explain its relevance to Islamic education. The command to read in Surah Al-'Alaq, verse 1, has a broad meaning; it is not limited to the act of reading texts but also encompasses efforts to understand, examine and study various phenomena of life as part of the process of seeking knowledge. This verse contains educational values that include literacy, intellectual development, spiritual nurturing, the strengthening of monotheistic awareness, and the encouragement of lifelong learning. The relevance of this verse to Islamic education is evident in the importance of strengthening a culture of literacy, the integration of knowledge and faith, the development of research-based learning, and the nurturing of learners who possess a balanced intellectual and spiritual intelligence. Thus, Surah Al-'Alaq, verse 1, can be understood as the conceptual foundation of Islamic education, which encourages the development of knowledge oriented towards divine and humanitarian values.